PRACTICAL ASPECTS OF THE PROSTHETIC REHABILITATION OF KENNEDY 1 CLASS EDENTATION - Magda-Ecaterina Antohe; Doriana Agop Forna; Cristina Iordache; Norina Consuela Forna (Romanian Dental Association for Education, 2019)
The purpose of the study is materialized by assessing the possibilities and limits in the treatment of partial protuberance with skeletal prostheses using special elements of maintenance, support and stabilization, depending on the clinical picture specific to each patient. The factual material was represented by a group of 51 patients diagnosed with partial exdended and subtotal edentation, aged 40 to 60, age range almost synonymous with the targeted pathology and accompanied by the whole range of changes and impairments of local parameters, locoregional and generalized ones, the latter having a particularly important role in targeting the therapeutic plan . We have highlighted the increased prevalence of Kennedy first Class among patients with partial extended edentation and association with other edentational classes in the field of removable prostheses, which argues the importance and contribution of removable solutions in ameliorating edema changes and the impact of treatment prosthetically removable on the quality of the patients' lives.